THE ART OF KELLY MODIFIED SURGICAL CORRECTION OF STRESS URINARY INCONTINENCE - Mercado, María (2015)
OBJECTIVE.- To determine the results of the modified Kelly technique for the surgical repair of stress urinary incontinence (SUI). DESIGN: Transversal retrospective analytical study. Setting: Police Central Hospital Gynecology Service, a teaching hospital. MATERLAL AND METHODS.- Study of 110 captive patients who had surgical intervention for SUI by the modified Kelly suture vaginal technique during 1995 and with 5-year follow-up. SPSS program and chi square test with statistical significance p < 0,05 were used for tabulation and data analysis, RESULTS: From the 110 patients 71,8% were postmenopausal. SIU presented most frequently in women in their 6th and 7th decades and the associated moderate cystocele was directly related to the number of vaginal deliveries. Anterior posterior colporrhaphy (APC) plus modified Kelly technique was performed in 75,5% of cases and vaginal hysterectomy plus APC plus modified Kelly suture in 23,6%; 52,7% presented postoperative complications, mainly urinary tract infection (27,39%) and urinary retention (25,5%). Foley catheter was usually removed on the third post operative day and 98% of patíents díd not present SUI recurrence at 5 years follow-up. CONCLUSIONS.- The modified Kelly suture vaginal technique for cysiocele-associated SUI repair presents postoperative complications but seems efficacious at the long term.